Oil Palm Plantations, Forest Conservation and Indigenous Peoples in West Papua Province: What Lies Ahead? - Runtuboi, Yubelince Y.; B. Permadi, Dwiko; Sahide, Muhammad Alif K.; Maryudi, Ahmad (Forest and Society, 2021)
Oil palm plantations are currently expanding to the eastern part of Indonesia, especially in West Papua province. Many oil palm permits issued in West Papua occupy intact biodiversity-rich forest areas which have essential value for indigenous Papuans' socio-cultural life. This article discusses expansion of oil palm plantations in West Papua province, and its impacts on forests and indigenous people. It also assesses whether the plantations fit the Special Autonomy Law and Sustainable Development Regulation goals of the province. In general, plantations are being established in forest areas, and further planned expansion threatens intact and biodiversity-rich forests. In addition, plantation development rarely considers the socio-cultural issues of indigenous Papuans. As a result, customary rights and institutions are commonly overlooked, undermined, or violated. Oil palm plantations are not necessarily compatible with sustainable development regulation goals, and need to reconcile its overall economic and conservation agenda.